Muslim holidays - Winchester, Faith (Mankato, Minn. : Bridgestone Books, 1996)
Briefly describes the beliefs of Muslims and eight of the special celebrations that are part of the Islamic faith.
Includes bibliographical references (p. 24) and index.
4.6
K-3
Keywords: Holidays -- Islamic countries -- Juvenile literature; Muslims -- Social life and customs -- Juvenile literature; Fasts and feasts -- Islam; Islam -- Customs and practices; Muslims -- Social life and customs; Islamic holidays; Islam; Muslims -- Social life and customs; Holidays; Muslims; Fasts and feasts -- Islam; Islam -- Customs and practices